Effectiveness of Different Competition Environments and Thier Potential Use for the Development of Sweet Corn Inbreds and Hybrids (Zea mays L.) - Nguyen Tien Truong; Krisda Samphantharak; Vatcharee Lertmongkol (Agriculture and Natural Resources, 2006)
Family selection was applied in segregated populations of three single crosses in three different environments; low-competition environment in non-replicated honeycomb design (HC), high plant density environment (HD) and alternate environments of the first two methods (HC-HD). Each family composed of 9 S2 lines which was equally separated into 3 sets. Each set was applied into each selection environment and selfed to obtain 3 S3HC, 3 S3HD and 3 S3 HC-HD for each family. Diallel cross was applied within each set and the best recovered single cross hybrid (A/A’) of each set was testcrossed to corresponding lines within set to obtain 27 within set testcross hybrids (recovered three–way hybrids, A/A’//A’’). Simultaneously, the 9 best recovered single cross hybrids were diallel crossed to form 36 sister line crosses, (A/A’//BB’). Selection for inbred line performance per se was effective in the respective manners; under low-competition environment in non-replicated honeycomb design, alternate environments and high plant density environment. High yield lines had a tendency to render high yield hybrids. However, ranking of yield could not be used as criterion for combining ability of lines. The sister line crosses either H × H or H × L were equally expressed in hybrid performances.